Low-temperature synthesis of condensed zinc and cobalt (II) phosphate solid solution with the given anion structure - Antraptseva, N.M.; Solod, N.V.; Kochkodan, O.D. (Functional Materials, 2019)
The anionic composition of heat treatment products of crystalline hydrates of the general formula Zn₁-xCox(H₂PO₄)₂·2H₂O (0 < x < 1.00) under isothermal conditions is determined. Quantitative dependences of the content of condensed phosphates with different anion structure (linear and cyclic) and phosphate acids, which released as intermediate products, on the temperature regime and roasting duration were established. The influence of cation nature is shown. The conditions of the formation and thermal stability of everyone linear condensed phosphates with n = 2-8 and the solid solution of cyclotetraphosfates of the composition Zn₁-xCoxP₄O₁₂ (0 < x < 1.00) are concretized.